UFO Mushroom Invasion - Marina, Shirakawa (Living the Line LLC, 2024)
A flying saucer crashes deep in the mountains of Japan. Wary of the hyper-intelligent beings they find inside, the government hides from the public all news of the alien craft. But it’s not the strange visitors themselves that they should be afraid of―the real danger is the parasitic spores smuggled aboard! Will Earth survive the UFO MUSHROOM INVASION?!